Neutrinos from type Ia supernovae: the gravitationally confined detonation scenario - Wright, Warren P.; Röpke, Friedrich (Physical review, 2017)
Despite their use as cosmological distance indicators and their importance in the chemical evolution of galaxies, the unequivocal identification of the progenitor systems and explosion mechanism of normal type Ia supernovae (SNe Ia) remains elusive. The leading hypothesis is that such a supernova is a thermonuclear explosion of a carbon-oxygen white dwarf, but the exact explosion mechanism is still a matter of debate. Observation of a galactic SN Ia would be of immense value in answering the many open questions related to these events. One potentially useful source of information about the explosion mechanism and progenitor is the neutrino signal because the neutrinos from the different mechanisms possess distinct spectra as a function of time and energy. In this paper, we compute the expected neutrino signal from a gravitationally confined detonation (GCD) explosion scenario for a SN Ia and show how the flux at Earth contains features in time and energy unique to this scenario. We then calculate the expected event rates in the Super-K, Hyper-K, JUNO, DUNE, and IceCube detectors and find both Hyper-K and IceCube will see a few events for a GCD supernova at 1 kpc or closer, while Super-K, JUNO, and DUNE will see events if the supernova is closer than ∼0.3 kpc. The distance and detector criteria needed to resolve the time and spectral features arising from the explosion mechanism, neutrino production, and neutrino oscillation processes are also discussed. The neutrino signal from the GCD is then compared with the signal from a deflagration-to-detonation transition (DDT) explosion model computed previously. We find the overall event rate is the most discriminating feature between the two scenarios followed by the event rate time structure. Using the event rate in the Hyper-K detector alone, the DDT can be distinguished from the GCD at 2σ if the distance to the supernova is less than 2.3 kpc for a normal mass ordering and 3.6 kpc for an inverted ordering.